The Influence of Service Quality on Customer Satisfaction In SMEs – In Samosir - Dian Septiana Sari (Yayasan Multidimensi Kreatif, 2023)
The aim of this study, to test the effect of service Reliability (accuracy), Responsiveness (responsiveness), Assurance (security or safety), Empathy (attention) and Tangibles (physical condition) simultaneously affect the customer satisfaction of SMEs - in Samosir. This research is quantitative descriptive research is research that aims to decipher or describe the properties (characteristics) of a situation or object of research, which is conducted through the collection and analysis of quantitative data and statistical testing. This research test equipment using multiple linear regression models using the t test and F test F test results prove reliability variables (X1), responsivenes (X2), assurance (X3), empathy (X4) and tangibless (X5) simultaneously significant effect on Y (customer satisfaction). T-test results prove that the only variable responsivenes (X2), empathy (X4) and tangibless (X5) which significantly influence customer satisfaction.